(untitled) (Práxis Educativa, 2020)
In the context of the progressive increase of immigrants in Chile, this paper aims at characterizing the main challenges that arise in school management, to integrate foreign immigrant students in schools in the Talca district, Maule Region in Chile. The study is qualitative in nature and the analysis is carried out through research case studies, using content analysis techniques. For this purpose, in-depth interviews were conducted with members of management teams from three educational establishments of Basic Education, each belonging to one of the three administrative units that characterize the mixed provision of the Chilean school system. The results of the study yielded organized evidence in the dimensions of policies, practices and procedures used in the school management of educational establishments, in relation to schooling processes and pedagogical inclusion of foreign immigrant students. Keywords: School directors. Education Management. Foreign immigrants. Schooling. Inclusion.